2018
DOI: 10.1037/hea0000578
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy combined with exercise for adults with chronic diseases: Systematic review and meta-analysis.

Abstract: Therapy combined with physical exercise for depression, anxiety, fatigue and pain in adults with chronic diseases: systematic review and meta-analysis. Health Psychology (accepted) 1 Declaration of interestAll authors declare that they have no competing interests for this work.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 92 publications
(115 reference statements)
1
35
0
Order By: Relevance
“…While the majority of these studies have been done to compare the effectiveness of BT to exercise interventions, fewer studies have been employed to examine the combined effect of exercise and BT (BT+Ex). Researchers have hypothesized that BT+Ex may augment the effectiveness of treatment [20]. Ernst et al [21] hypothesized that the exercise-induced upregulation of brain-derived neurotrophic factor (BDNF) promotes brain neurogenesis, resulting in a reduction of symptoms associated with depression and anxiety [21].…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of these studies have been done to compare the effectiveness of BT to exercise interventions, fewer studies have been employed to examine the combined effect of exercise and BT (BT+Ex). Researchers have hypothesized that BT+Ex may augment the effectiveness of treatment [20]. Ernst et al [21] hypothesized that the exercise-induced upregulation of brain-derived neurotrophic factor (BDNF) promotes brain neurogenesis, resulting in a reduction of symptoms associated with depression and anxiety [21].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, eight papers were rejected because they were not about CBT, 11 were not meta-analyses, 25 were not about anxiety disorders, 31 were limited in their population scope, two were not about treatment efficacy, five were limited to Internet or computer-based intervention, and six were about CBT-VRexp or MBT. Of the eight remaining papers, one was rejected because it was limited in scope (group therapy for PTSD; Schwartze et al, 2019), one was too restrictive on the measure of outcome to allow comparisons (remission rate; Springer et al, 2018), two studied the effect of added interventions to CBT (Bernard et al, 2018;Marker and Norton, 2018), and two were limited to primary care settings without information about specific anxiety disorders (Zhang et al, 2019a,b). Since Barry et al (2018) did not provide information about RCTs, we favored Carpenter et al 2018for our study (see Supplementary Material 3).…”
Section: Resultsmentioning
confidence: 99%
“…7 Therapeutic lifestyle changes that target diet and exercise are known to positively influence depressed mood. 34,35 We have previously shown that standard cardiac rehabilitation is effective in not only reducing mortality risk but also in reducing depression symptoms in HF, 7 and that other forms of behavioral interventions favorably affect the somatic/affective but not the cognitive/affective depressive symptoms. 17 Given the elevated IL-6, TNF-R1, and sST2 levels in stage B HF patients with both T2DM and depressed mood, additional attention and interventions to forestall potential transition to symptomatic stage C HF may be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, depressive symptoms and depressed mood are significant predictors of morbidity and mortality in cardiac and noncardiac populations . Therapeutic lifestyle changes that target diet and exercise are known to positively influence depressed mood . We have previously shown that standard cardiac rehabilitation is effective in not only reducing mortality risk but also in reducing depression symptoms in HF, and that other forms of behavioral interventions favorably affect the somatic/affective but not the cognitive/affective depressive symptoms …”
Section: Discussionmentioning
confidence: 99%